International public administrations in environmental governance the role of autonomy, agency, and the quest for attention - Jörgens, Helge 1967-; Kolleck, Nina; Well, Mareike 1987- (Cambridge University Press, 2024)
Combining theoretical and empirical approaches, this book examines the role that international public administrations play in global environmental politics in the Anthropocene. With chapters written by leading experts in the field, this text offers fresh insight into how international bureaucracies shape global policies in the complex areas of climate change, biodiversity, and development policy. International public administrations are thus recognized as partially autonomous actors with their own interests and motivations, assuming the roles of managers, orchestrators, brokers, or attention-seekers. This comprehensive resource provides scholars and practitioners with valuable insight into environmental policymaking and how international public administrations might be transformed to better address the multiple, fundamental challenges of our century. This is one of a series of publications associated with the Earth System Governance Project. For more publications, see www.cambridge.org/earth-system-governance. This title is also available as Open Access on Cambridge Core.